2006
DOI: 10.1177/107110070602700803
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Moderate to Severe Hallux Valgus Deformity by a Modified Chevron Shaft Osteotomy

Abstract: Based on radiographic correction and clinical outcomes, this procedure is indicated for the treatment of moderate to severe hallux valgus deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 20 publications
3
21
0
3
Order By: Relevance
“…Sanhudo [23] retrospectively reviewed 50 feet with moderate to severe hallux valgus deformity in 34 patients with a mean FU of 30 months. There was a mean AOFAS score improvement of 39.6 (44.5 to 84.1) points.…”
Section: Discussionmentioning
confidence: 99%
“…Sanhudo [23] retrospectively reviewed 50 feet with moderate to severe hallux valgus deformity in 34 patients with a mean FU of 30 months. There was a mean AOFAS score improvement of 39.6 (44.5 to 84.1) points.…”
Section: Discussionmentioning
confidence: 99%
“…Par ailleurs, les résultats cliniques obtenus avec une technique mini-invasive sont comparables à ceux obtenus avec les principales techniques comme l'ostéotomie en chevron [6][7][8][9], l'ostéotomie de Scarf comme l'ont montré Freslon et al [10] et l'ostéotomie métatarsienne proximale [11,12].…”
Section: Discussionunclassified
“…Il en est de même par rapport aux techniques percutanées développées ces dernières années, avec ou sans ostéosyn-thèse [13][14][15][16][17][18] avec des scores fonctionnels postopératoires allant de 82 à 93,5 selon les auteurs [5][6][7][8][9][10][11][19][20][21][22].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As a rule, the distal osteotomy is used for the mild to moderate deformity, and the proximal osteotomy is used for the more severe deformity [35] . Recently it is reported that Chevron osteotomy is indicated for the treatment of moderate to severe hallux valgus deformities [46] . The preservation of dorsi-flexion in the first metatarsophalangeal joint is important in women, as any reduction will affect their ability to wear high-heeled shoes [15] .…”
Section: ~ 301 ~ International Journal Of Orthopaedics Sciencesmentioning
confidence: 99%